Italian Version of the Cornell Assessment of Pediatric Delirium: Evaluation of the Scale Reliability and Ability to Detect Delirium Compared to Pediatric Intensive Care Unit Physicians Clinical Evaluation - Fazio, Paola Claudia; Daverio, Marco; Masola, Maristella; D’Angelo, Igor; Frison, Sara; Zaggia, Cristina; Simeone, Silvio; Pucciarelli, Gianluca; Gregori, Dario; Comoretto, Rosanna; Amigoni, Angela (Frontiers in Pediatrics, 2022)
Background: Delirium is an acute brain dysfunction associated with increased length of hospitalization, mortality, and high healthcare costs especially in patients admitted to the pediatric intensive care unit (PICU). The Cornell Assessment of Pediatric Delirium (CAPD) is a screening tool for evaluating delirium in pediatric patients. This tool has already been used and validated in other languages but not in Italian. Objectives: To test the reliability of the Italian version of the CAPD to screen PICU patients for delirium and to assess the agreement between CAPD score and PICU physician clinical evaluation of delirium. Methods: Prospective double-blinded observational cohort study of patients admitted to a tertiary academic center PICU for at least 48 hours from January 2020 to August 2021. We evaluated intra- and inter-rater agreement using the Intraclass Correlation Coefficient (ICC). The ability of the scale to detect delirium was evaluated by comparing the nurses’ CAPD assessments with the clinical evaluation of a PICU physician with expertise in analgosedation using the area under the ROC curve (AUC). Measurements and Main Results: Seventy patients were included in the study. The prevalence of pediatric delirium was 54% (38/70) when reported by a positive CAPD score and 21% (15/70) when diagnosed by the PICU physician. The CAPD showed high agreement levels both for the intra-rater (ICC 1 0.98, 95% CI 0.97-0.99) and the inter-rater (ICC 2 0.93, 95% CI; 0.89-0.96) assessments. In patients with suspected delirium according to the CAPD scale, the observed sensitivity and specificity of the scale were 0.93 (95% CI 0.68-1.00) and 0.56 (95% CI 0.42-0.70), respectively. The AUC observed was 0.75 (95% CI 0.66-0.8490). Conclusions: The Italian version of the CAPD seems a reliable tool for the identification of patients at high risk of developing delirium in pediatric critical care settings. Compared to the clinical evaluation of the PICU physician, the use of the CAPD scale avoids a possible underestimation of delirium in the pediatric population.